2017
DOI: 10.1016/j.bbalip.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Breaking fat: The regulation and mechanisms of lipophagy

Abstract: Lipophagy is defined as the autophagic degradation of intracellular lipid droplets (LDs). While the field of lipophagy research is relatively young, an expansion of research in this area over the past several years has greatly advanced our understanding of lipophagy. Since its original characterization in fasted liver, the contribution of lipophagy is now recognized in various organisms, cell types, metabolic states and disease models. Moreover, recent studies provide exciting new insights into the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(130 citation statements)
references
References 130 publications
6
124
0
Order By: Relevance
“…It is now recognized that LD catabolism in hepatocytes is also regulated by degradation through autophagic mechanisms (lipophagy), which recently has been mechanistically linked to ATGL . We found that cyclin D1 inhibited autophagy in hepatic cells, as has been shown in other cell types .…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…It is now recognized that LD catabolism in hepatocytes is also regulated by degradation through autophagic mechanisms (lipophagy), which recently has been mechanistically linked to ATGL . We found that cyclin D1 inhibited autophagy in hepatic cells, as has been shown in other cell types .…”
Section: Discussionsupporting
confidence: 75%
“…We next examined proteins involved in lipolysis in hepatocytes. The initial step in cytoplasmic LD lipolysis is catalyzed by ATGL, which is recruited to the surface of LDs . The factors regulating hepatic ATGL activity are incompletely characterized, but this lipase is activated by binding to comparative gene identification‐58 (CGI‐58; gene name, Abdh5 ) and inhibited by G0S2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since PLIN1 and PLIN2 are targets for UPS degradation, it is possible that the UPS regulates LD function through effects on macrolipophagy. For a more extensive recent review of macrolipophagy see Schulze et al (34). …”
Section: Lipophagy: Ld Autophagymentioning
confidence: 99%